2021
DOI: 10.1007/s00590-021-03066-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of unstable pertrochanteric fractures in high-risk geriatric treated with external fixators

Abstract: Background: To review the outcome of high-risk geriatrics with unstable pertrochanteric fractures treated with external xator. Methods: Eighteen consecutive patients with pertrochanteric fractures were operated with external xator by using closed reduction technique. AO type (A2. 2, A2.3, A3.1, A.3.2 and A.3.3)) fractures were included in the study. Accompanying diseases, operating time, transfused blood units, duration of hospitalization, complications, healing time and mortality were recorded. Patients were … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…According to recent trials on external fixation devices, there was no long-term knee stiffness after 12 months. 16,17,21,22 Our last follow-up found that the hip's range of motion was normal.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…According to recent trials on external fixation devices, there was no long-term knee stiffness after 12 months. 16,17,21,22 Our last follow-up found that the hip's range of motion was normal.…”
Section: Discussionmentioning
confidence: 83%
“…Our research found that the average time of stay in the hospital was 1.80±0.95 days, which is much less than the average time recorded in published studies. 16,17,18 .The short amount of time that patients spend at the hospital before being operated on in this research. All of these factors, including the quickness of the surgery and the early postoperative mobility, led to the patient being discharged from the hospital earlier, recovering quicker, suffering fewer complications and deaths, and spending less money on care overall.…”
Section: Discussionmentioning
confidence: 98%